If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(7 + -3x) = (-6) (7 * 2 + -3x * 2) = (-6) (14 + -6x) = (-6) 14 + -6x = -6 Solving 14 + -6x = -6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + -6x = -6 + -14 Combine like terms: 14 + -14 = 0 0 + -6x = -6 + -14 -6x = -6 + -14 Combine like terms: -6 + -14 = -20 -6x = -20 Divide each side by '-6'. x = 3.333333333 Simplifying x = 3.333333333
| 4(M-5)=5(p-7) | | 4y=-3y+14 | | -y+96=208 | | k+13=8 | | 281=45-w | | 10y=7-7y | | y+1.88=4.91 | | 3x-5+4x=7 | | 2/78/21 | | 5(4x-10)=30 | | 3/4j-10≥5 | | k-5=5 | | 7(8-4m)=140 | | M(7m+14)=693 | | r-9=2 | | r-8=6 | | -.25(16x-12)+3=-6 | | -38=-10y | | 8x-11-5x+19= | | b+12=27 | | 10y-25=12 | | 2/7(4m-19)=12 | | 9-3(n-5)=20 | | 2x+8x=-32 | | -5e-4e= | | 35=-5/3u | | -4d+6d= | | x^2+19x-83=0 | | 12.75y+12.00=15.75x | | 3x-6+5=2(5x-4) | | y-84/2=7 | | X^2+DX-2D^2=0 |